Odpowiedź:
[tex]x = m - 2y \\ nx - 4y = 4 \\ \\ x = m - 2y \\ n(m - 2y) - 4y = 4 \\ \\ x = m - 2y \\ nm - 2ny - 4y = 4 \\ \\ x = m - 2y \\ y(- 2n - 4) = 4 - nm \\ \\ x = m - 2y \\ y = \frac{4 - nm}{ - 2n - 4} [/tex]
[tex]x = m - 2( \frac{4 - nm}{ - 2n - 4}) \\ y = \frac{4 - nm}{ - 2n - 4} = \frac{( - 1)(nm - 4)}{( - 1)(2n + 4)} = \frac{nm - 4}{2n + 4} \\ \\ x = m + \frac{ - 8 + 2nm}{ - 2n - 4} = m \frac{ - 2n - 4}{ - 2n - 4} + \frac{ - 8 + 2nm}{ - 2n - 4} = \frac{ - 2nm - 4m - 8 + 2nm}{ - 2n - 4} \\ = \frac{ - 4m - 8}{ - 2n - 4} = \frac{ 4m + 8}{ 2n + 4} [/tex]